(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
The article examines the concept and essence of technical support, its role in evaluating promising projects, trends in the development of financing investment projects, issues of raising funds and factors influencing their timely development. The foreign experience of banks in attracting credit resources from international financial organizations has been studied. In addition, the possibilities of applying international experience in the field of technical evaluation of projects, ways of cooperation with international financial institutions such as the International Finance Corporation (IFC), the International Bank for Reconstruction and Development (IBRD), the European Bank for Reconstruction and Development (EBRD) and the Asian Development Bank (ADB) were considered.